Analysis of Difficulties in Understanding Arabic Text: A Case Study at Al-Azhar Yogyakarta Boarding School - Saadah, Badriyyah; Isnaini, Rohmatun Lukluk; Kahfi, Nazih Sadatul; Ramadhani, Naili Izzah; Arju, Salsabila (Insyirah: Jurnal Ilmu Bahasa Arab dan Studi Islam, 2025)
A deep comprehension of learning materials is vital for meaningful and lasting education. When understanding is lacking, learning becomes superficial and fails to leave a significant impact. This study investigates the challenges students encounter in comprehending Arabic texts at Al-Azhar Yogyakarta boarding school, focusing on the key factors that hinder their textual understanding. Employing a qualitative descriptive method, data were collected through observations, interviews, and document analysis. The findings identify several obstacles to adequate comprehension, including linguistic challenges such as limited vocabulary, complex syntactic structures, and unfamiliarity with context. Pedagogical issues also emerged, particularly teaching methods that inadequately address diverse learner needs. Furthermore, student motivation and prior exposure to Arabic significantly influence their ability to engage with the texts. To address these issues, the study recommends strategies such as contextualized instruction, interactive teaching techniques, and personalized learning approaches. The results underscore the need for curricular reforms that integrate contemporary pedagogical practices and educational technologies. By confronting these challenges, the study aims to enhance students’ comprehension of Arabic texts, improve learning outcomes, and provide a foundation for future research on effective methods of Arabic language instruction in similar educational environments.